Perancangan Aplikasi Mobile Berbasis Flutter untuk Pemantauan Data Sensor IoT: Solusi bagi Manajemen Suhu dan Kelembapan - Arif Setia Sandi Ariyanto; Iis Setiawan Mangku Negara; Deny Nugroho Triwibowo; Yanuar Feriyanto (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study developed a mobile application based on Flutter to monitor Internet of Things (IoT) sensor data for real-time measurement of temperature and humidity. The system utilizes a DHT22 sensor connected to an ESP32 microcontroller, transmitting data via the MQTT protocol. The data is stored in a MySQL database hosted on a designated server. The mobile application offers an interactive interface to display real-time data, historical graphs, and automatic notifications when environmental parameters exceed predefined thresholds. Testing was conducted using the User Acceptance Testing (UAT) method involving 20 respondents. The results indicate a high level of application success, with an average user satisfaction rate of 93% for ease of login, 90% for the interface, 90% for data processing speed, and 93% for notification accuracy. By integrating IoT, Flutter, and MySQL technologies, this application provides an efficient digital solution for environmental management, with potential for development across various industrial sectors requiring such capabilities.